The determination of cis and trans fatty acid isomers in partially hydrogenated plant oils - Marais, Christiaan De Wet (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2007.